Learning Hydraulic Engineering from Site Visit and Open Book Assessment - Anwar, Faisal (2018)
Due to the introduction of computer based program and reduction of face-to-face contact hours, many higher education institutions are cutting site visits and field works from their curriculum. But engineering is an applied science to the real-world problems and the engineering education needs hands-on training. Because of this, fieldworks and site visits are essential components of engineering course curricula. Upon completion of lecture on dam engineering, a visit to a dam site was conducted for final year civil engineering students, which was followed by an open book assessment after one week of visit. In order to investigate the student learning on hydraulic engineering from site visit and its subsequent open book assessment, a questionnaire survey was conducted after the open book test. The survey instruments consist of two sections. One section has 9 questions on student learning from site visit and second section consists of 10 questions on learning from open book assessment. The results revealed that students are motivated (87% agreement; n=39) for site learning because it provides work-integrated learning experiences (also 87% agreement; n=39). It also shows that an open book assessment is an excellent way of learning to be a professional engineer (92% agreement; n=48). Student performances on site learning show that 78% of the students got mark more than 70% in the test achieving significant learning outcomes. This also indicates that the open book assessment motivates students’ independent learning but there is a need to train students what information they need to bring because many of them found wasting times flipping through the site visit notes/books.